20 years of International Corporate Governance research - Vivas-Crisol, Laura; Martínez-Blasco, Mónica; García-Blandón, Josep (Revista General de Información y Documentación, 2012)
International Corporate Governance is a topic of growing interest. Despite all the results that have led years of research, this issue remains an interesting topic in Economics and Finance. This article examines the scientific literature on international corporate governance since the first article was published in 1992. The data is obtained from the database ISI Web of Science, resulting in 338 articles that have been analyze to obtain the most cited articles, the evolution in the number of publications, the authors and journals cited and Index of Scientific Collaboration.